Harnessing croconaine organic photosensitizers for a milder surface-mediated transfection - Ferdinandus (2024)
Polydopamine-based materials, notably Polydopamine-polyethyleneimine (PDA-PEI), have gained considerable interest for surface-mediated transfection. However, the high laser power density required to achieve high transfection efficiency poses a significant challenge in preserving cell viability. An organic photosensitizer CRO32TMI was developed to improve the photothermal conversion capability of PDA-PEI. The modified PDA-PEI-CRO32TMI exhibited remarkable photothermal and photostability properties upon NIR irradiation, enabling it to achieve better transfection efficiency at lower laser power density as compared to the traditional solution or lipid-based transfection methods.